Team science and the physician–scientist in the age of grand health challenges. Issue 1 (5th October 2017) - Steer, Clifford J.; Jackson, Peter R.; Hornbeak, Hortencia; McKay, Catherine K.; Sriramarao, P.; Murtaugh, Michael P.
Abstract: Despite remarkable advances in medical research, clinicians face daunting challenges from new diseases, variations in patient responses to interventions, and increasing numbers of people with chronic health problems. The gap between biomedical research and unmet clinical needs can be addressed by highly talented interdisciplinary investigators focused on translational bench‐to‐bedside medicine. The training of talented physician–scientists comfortable with forming and participating in multidisciplinary teams that address complex health problems is a top national priority. Challenges, methods, and experiences associated with physician–scientist training and team building were explored at a workshop held at the Second International Conference on One Medicine One Science (iCOMOS 2016), April 24–27, 2016, in Minneapolis, Minnesota. A broad range of scientists, regulatory authorities, and health care experts determined that critical investments in interdisciplinary training are essential for the future of medicine and healthcare delivery. Physician–scientists trained in a broad, nonlinear, cross‐disciplinary manner are and will be essential members of science teams in the new age of grand health challenges and the birth of precision medicine. Team science approaches have accomplished biomedical breakthroughs once considered impossible, and dedicated physician–scientists have been critical to these achievements. Together, they translate into the pillars of academic growth and success.